Administration of zinc complex of acetylsalicylic acid after the onset of myocardial injury protects the heart by upregulation of antioxidant enzymes - Korkmaz-İçöz, Sevil; Atmanli, Ayhan; Radovits, Tamás; Li, Shiliang; Hegedűs, Péter; Ruppert, Mihály; Brlecic, Paige; Yoshikawa, Yutaka; Yasui, Hiroyuki; Karck, Matthias; Szabó, Gábor (The journal of physiological sciences, 2016)
We recently demonstrated that the pre-treatment of rats with zinc and acetylsalicylic acid complex in the form of bis(aspirinato)zinc(II) [Zn(ASA)2] is superior to acetylsalicylic acid in protecting the heart from acute myocardial ischemia. Herein, we hypothesized that Zn(ASA)2 treatment after the onset of an acute myocardial injury could protect the heart. The rats were treated with a vehicle or Zn(ASA)2 after an isoproterenol injection. Isoproterenol-induced cardiac damage [inflammatory infiltration into myocardial tissue, DNA-strand breakage evidenced by TUNEL-assay, increased 11-dehydro thromboxane (TX)B2-levels, elevated ST-segment, widened QRS complex and prolonged QT-interval] was prevented by the Zn(ASA)2 treatment. In isoproterenol-treated rats, load-independent left ventricular contractility parameters were significantly improved after Zn(ASA)2. Furthermore, Zn(ASA)2 significantly increased the myocardial mRNA-expression of superoxide dismutase-1, glutathione peroxidase-4 and decreased the level of Na+/K+/ATPase. Postconditioning with Zn(ASA)2 protects the heart from acute myocardial ischemia. Its mechanisms of action might involve inhibition of pro-inflammatory prostanoids and upregulation of antioxidant enzymes.